We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
77
2
avatar+327 

Hard to figure out lol

 

y=x^2−3x+7

 

y=3x−2

 

What is the y-coordinate of the solution?

 

Thanks a million!! :)

 Feb 25, 2019
 #1
avatar+100570 
+2

y=x^2−3x+7

 

y=3x−2

 

Set yhe y's equal and we have that

 

x^2 - 3x + 7  =   3x - 2          subtract 3x / add 2   from/to both sides

 

x^2 - 6x + 9   =  0        factor

 

(x - 3)^2 = 0        which implies that x = 3

 

So.......plug 3 into either function  and we get that   y = 3(3) - 2   =  7    

 

 

cool cool cool

 Feb 25, 2019
 #2
avatar+647 
+2

Set it so that \(x^2-3x+7=3x-2\) .

Now bring over to the left side: \(x^2-6x+9=0\)

We can find out that \(x=3\).

 

Now plug it in to \(y=3x-2 => y=3(3)-2 => y=7\)

 

Therefore, the y-coordinate is 7.

 

You are very welcome!

:P

 Feb 25, 2019

3 Online Users